Hubungan antara Kesanggupan Berpikir Formal ala Piaget dan Prestasi Belajar Pengetahuan Dasar MIPA Siswa Kelas V Sekolah Dasar - Soetopo Soetopo (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
The Relationship between Ability to Perform Formal Operations of Piaget and Fifth Graders Achievement in Science. The purpose of the study was to find out the relationship between the ability to perform formal operations of Piaget and achievement in science. A number of 598 fifth graders of 12 elementary schools were involved. Interview and test were used to collect the data, which were then analyzed using statistics of percentages, correlation analyses, and multiple regression. The results indicate that girls are proportionally more able to perform formal operations than boys and that the ability has positive relationship to students' achievement in science.